2019
DOI: 10.5194/nhess-19-1755-2019
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale assessment of cross-boundary wildfire events in the western United States

Abstract: Abstract. We report a fine-scale assessment of cross-boundary wildfire events for the western US. We used simulation modeling to quantify the extent of fire exchange among major federal, state, and private land tenures and mapped locations where fire ignitions can potentially affect populated places. We examined how parcel size affects wildfire transmission and partitioned the relative amounts of transmitted fire between human and natural ignitions. We estimated that 85 % of the total predicted wildfire activi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…state, family forest) experience more incoming fire transmitted from other ownerships than large parcels (e.g. USFS) (Palaiologou et al 2019). Federal landowners in our cases were usually slower than other landowner types to complete treatments, a concern among nonfederal owners who worried a wildfire would occur and compromise their efforts.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…state, family forest) experience more incoming fire transmitted from other ownerships than large parcels (e.g. USFS) (Palaiologou et al 2019). Federal landowners in our cases were usually slower than other landowner types to complete treatments, a concern among nonfederal owners who worried a wildfire would occur and compromise their efforts.…”
Section: Discussionmentioning
confidence: 68%
“…Wildfire risk reduction in multi-ownership landscapes is a collective action problem for both ecological and social reasons. From an ecological standpoint, wildfires can burn large areas (>40 000 ha) and wildfire transmission occurs across land ownerships , Hessburg et al 2015, Palaiologou et al 2019. It is neither practical nor necessary to treat hazardous fuels everywhere to reduce wildfire risk; nevertheless, thousands of hectares must be treated to change fire behavior and reduce its severity (Finney et al 2007, North et al 2012, Krofcheck et al 2017, Tubbesing et al 2019.…”
Section: Background: Wildfire As a Collective Action Problem In Multimentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation for the BAU option was run 100,000 times. The fireshed (e.g., [26]) was estimated as the convex area for which a potential ignition could lead to a wildfire that would partially burn the Alvares parish. To reduce computational time, only the ignitions overlapping the fireshed area (ca.…”
Section: Simulating the Different Fuel Management Scenariosmentioning
confidence: 99%
“…Science can contribute with knowledge and tools for more effective landscape fuel management, thus improving planning and decision-making. Previous research has shown how fire spread simulation tools can be used to assess wildfire exposure at the landscape level [19][20][21], quantify associated risk [22][23][24], study wildfire transmission [25,26] and identify optimal fuel treatment location [27,28]. These simulation tools have also proven useful to quantify the potential impact of climate change on wildfire incidence [29] and of mitigation measures on post-fire erosion and water contamination [30,31].…”
Section: Introductionmentioning
confidence: 99%